2019
DOI: 10.9770/jesi.2019.7.2(41)
|View full text |Cite
|
Sign up to set email alerts
|

How enterprise risk management (erm) can affect on short-term and long-term firm performance: evidence from the Iranian banking system

Abstract: Enterprise risk management (ERM) has emerged as a more integrated risk management (IRM) framework in recent years. Many studies have been conducted in recent years to determine the effects of ERM implementation on other parts of an organization. The purpose of this research was to explore the relationship between ERM implementation and organizational performance. The research sample consisted of Iranian banks that either had a license from the central bank of Iran (CBI) or were active in the stock market. A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Another approach is to increase the effectiveness of management methods that affect risks in the activities of companies, including information (Grenčíková et al, 2019). Nasr et al (2019) suggested to create the integrated risk management framework for firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another approach is to increase the effectiveness of management methods that affect risks in the activities of companies, including information (Grenčíková et al, 2019). Nasr et al (2019) suggested to create the integrated risk management framework for firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Djalilov et al (2015), Vasylieva et al (2014) proved that corporate social responsibility has a moderate positive effect on banks' performance. It is worth to pay attention to the existing short-term impact in banks' efficiency growth due to social responsible banks' activities (Vasileva & Lasukova, 2013;Zhu et al, 2017), while implementation of new system of internal management has rather long-term effect (Nasr et al, 2019). At the same time the intensity of corporate social responsibility are defined by informational development (Hammerström et al, 2019;Bilan et al, 2019c).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning multiple stakeholders can lower risks and in return ENTREPRENEURSHIP AND SUSTAINABILITY ISSUES ISSN 2345-0282 (online) http://jssidoi.org/jesi/ 2020 Volume 7 Number 3 (March) http://doi.org/10. 9770/jesi.2020.7.3(71) improve short term and long term performance (Nasr et al, 2019). A large number of positive or negative interests are actually affected in different stages of a project from start to end.…”
Section: Introductionmentioning
confidence: 99%